ANALISIS PERBANDINGAN PEMBEBANAN PAJAK PENGHASILAN PASAL 21 ANTARA METODE NET BASIS DAN METODE GROSS UP - Diana Nastiti; Naning Fatmawatie; Wibowo Andoko (CAHAYA AKTIVA, 2018)
Every Manager seeks to maximize the welfare of the owners of the company to maximize the value of the company, made a profit as desired. To pursue maximum profit, the company made various efforts. One such effort is to save tax through income tax calculation article 21 employees using such Calculation Method Net Base Method in which the withholding tax is borne by the employees of the company and Gross Up Method which is where the company's tax cuts giving tax allowances PPh article 21 employees. The use of this methods in addition to maximizing the company's profit is also meant to motivate employees to be more productive. The purpose of this study was to analyze the comparison of the use of the method and the Base Net Gross Up method in calculating the income tax of Article 21 in the form of salaries and employee benefits of this research include comparative descriptive research with quantitative measurement in the form of payroll and employee benefits. Results from this study in the comparative use of both methods is concluded Compared Net method, calculation using the method of Gross up more benefit both parties, both employees and the Company. The company should use the method of Gross Up in the calculation of income tax article 21 employees.  Keywords: net basis, gross up, tax income